Development of Cultural Literacy through the Construction of the Matabesi Tribe Fohoraik Museum (Research Conducted at the Traditional House of the Matabesi Tribe, Umanen Village, West Atambua District, Belu Regency) - Seuk Asa, Sefrina Maria; Hum, M; Sae, Donatus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The Matabesi Traditional House Phobia Museum is located in Umanen Village, West Atambua District, Belu Regency. The Fohoraik Museum was built with the aim of storing cultural documentation of the Matabesi Tribe in physical and non-physical forms. The museum became one of the centers for the study of culture and philosophy of the Matabesi Tribe. The philosophy of the Matabesi Tribe as a non-physical culture is neter taek (mutual respect), notar no kbadan, ukun badu, hadomi no hadosan, hadinan no haklaran.